Peripheral vision and back tuck somersaults - Davlin, C. D.; Sands, W. A.; Shultz, B. B. (Perceptual and Motor Skills, 2001)
Although vision appears to enhance performance of somersaulting skills, few studies have investigated the source (foveal or ambient) of useful visual cues that can potentially be used by gymnasts during a somersault. Therefore, the primary objectives were to investigate the possible role of peripheral vision in the control of orientation and landing balance in a back tuck somersault. 10 female gymnasts (age = 11.6 +/- 2.7 yr., competitive level = 8 +/- 1.2, training time in gymnastics = 5.9 +/- 1.6 yr.) performed back tuck somersaults under four visual conditions (full visual field, horizontal peripheral vision limited to 100 degrees, horizonal peripheral vision limited to 60 degrees, and no vision) while wearing electromagnetic sensors that allowed automatic digitizing. Analysis yielded no statistically significant difference on any of the kinematic variables among vision conditions. Despite limiting the gymnasts' available horizontal peripheral vision, joint angles, angular velocities, and timing remained very similar. There were no statistically significant differences in landing balance between the conditions of full vision, 100 degrees peripheral vision, and 60 peripheral vision. However, gymnasts were less stable at landing when vision was absent as compared to the three other vision conditions.